Almost famous [videorecording (DVD)] - Crowe, Cameron, 1957-; Crowe, Cameron, 1957-; Crudup, Billy, 1968-; McDormand, Frances; Hudson, Kate, 1979-; Lee, Jason, 1970-; Fugit, Patrick, 1982-; Paquin, Anna; Balk, Fairuza; Taylor, Noah; Deschanel, Zooey, 1980-; Fallon, Jimmy; et al. (DreamWorks Home Entertainment, 2001)
It's the opportunity of a lifetime when teenage reporter William Miller lands an assignment from Rolling Stone magazine. Despite the objections of his protective mother, William hits the road with an up-and-coming rock band and finds there's a lot more to write home about than the music.